Handbook of Anthropometry 2012
DOI: 10.1007/978-1-4419-1788-1_117
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometry and Exercise in Obesity

Abstract: This chapter aims to review the effects of exercise on body measurements in overweight and obese people. Firstly, obesity is described in detail with regard to frequently associated medical problems and weight-related health risk. The necessity of the inclusion of an exercise training program in obesity management is underlined, and exercise training and exercise prescription for obese patients described. An overview of the anthropometric measurements used in assessing body fat distribution and monitoring the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The WC was measured at the midpoint of the distance between the lowest rib and iliac crest with the non-elastic tape. [16] All of the anthropometric measurements were performed and recorded by a single investigator.…”
Section: Assessmentmentioning
confidence: 99%
“…The WC was measured at the midpoint of the distance between the lowest rib and iliac crest with the non-elastic tape. [16] All of the anthropometric measurements were performed and recorded by a single investigator.…”
Section: Assessmentmentioning
confidence: 99%
“…Because health and body composition are related. Several research studies indicated the benefits of various physical activities and exercises, such as exercise training [10], aerobic training [11], and resistance training [12]. The focus of this study was resistance training.…”
Section: Introductionmentioning
confidence: 99%